The effects of brand collaboration, brand image, and digital campaign on purchase intention in the digital society: The case of Extra Joss × Agak Laen - Umi Cholifah; Rina Muskamah; Silvy Dewi Anggraini; Novia Isriyah; Reni Kumalasari; Putri Nurus Sa'idah; Regita Nuruz Zahro (Societa: Journal of Society and Change, 2026)
Brand rejuvenation strategies through brand collaboration are increasingly adopted to attract public attention; however, limited evidence explains the simultaneous effects of Brand Collaboration, Brand Image, and Digital Campaign on consumers' Purchase Intention. This study aims to examine the influence of these three variables on Purchase Intention in the Extra Joss × Agak Laen collaboration. A quantitative survey was conducted involving 120 respondents who had been exposed to the collaboration campaign through social media, and the data were analyzed using multiple linear regression with IBM SPSS Statistics. The findings reveal that Brand Collaboration, Brand Image, and Digital Campaign have positive and significant effects on Purchase Intention, with Brand Image emerging as the strongest predictor. The proposed model explains 63.8% of the variance in Purchase Intention. These findings highlight that brand rejuvenation, supported by a strong brand image and effective digital communication, can enhance public purchase intention and provide practical guidance for companies in developing marketing strategies that are more responsive to changing consumer behavior. Abstrak Strategi brand rejuvenation melalui kolaborasi merek semakin banyak diterapkan untuk menarik perhatian masyarakat, namun masih terdapat kesenjangan mengenai pengaruh simultan Brand Collaboration, Brand Image, dan Digital Campaign terhadap Purchase Intention konsumen. Penelitian ini bertujuan menganalisis pengaruh ketiga variabel tersebut terhadap Purchase Intention pada kolaborasi Extra Joss × Agak Laen. Penelitian menggunakan pendekatan kuantitatif dengan metode survei terhadap 120 responden yang mengetahui kampanye kolaborasi melalui media sosial, kemudian dianalisis menggunakan regresi linear berganda dengan bantuan IBM SPSS Statistics. Hasil penelitian menunjukkan bahwa Brand Collaboration, Brand Image, dan Digital Campaign berpengaruh positif dan signifikan terhadap Purchase Intention, dengan Brand Image sebagai variabel yang memiliki pengaruh paling dominan. Model penelitian mampu menjelaskan 63,8% variasi Purchase Intention. Temuan ini menegaskan bahwa strategi brand rejuvenation yang didukung citra merek yang kuat dan komunikasi digital yang efektif mampu meningkatkan minat beli masyarakat serta menjadi acuan bagi perusahaan dalam merancang strategi pemasaran yang lebih adaptif terhadap perubahan perilaku konsumen.